Molecular genetic markers of atrial fibrillation - A. V. Ponasenko; M. Y. Sinitsky; M. V. Khutornaya (Бюллетень сибирской медицины)
Atrial fibrillation (AF) is the supraventricular form of tachyarrhythmia characterized by uncoordinated atrial stimulation and manifested in the increased frequency of their contraction. The frequency of this pathology directly correlates with the patients’ age and reaches 50% in an older age group. This fact determines the need for search of any markers of individual AF risk, which may contribute to an increase in the effectiveness of preventive actions. Among such markers, polymorphic variants of genes involved in the pathogenesis of AF are the most promising markers. This review discusses the results of studying the genetic markers of the AF development, as well as the possibility of their use as predictors of this pathology.